Rental house [large type] - Wang, Weike (Random House Large Print, 2024)
"Keru and Nate first meet in college, brought together by a joke at a Halloween party (would a "great white" costume mean dressing like a shark or a privileged Ivy League student?) and marrying a few years later. Misfits in their own families, they find in each other a feeling of home. Keru is the only child of strict, well-educated Chinese immigrant parents who hold her to impossible standards even as an adult ("To use a dishwasher is to admit defeat," says her father). Nate is from a rural, white, working class family that has never trusted his intellectual ambitions or - now - the citizenship status of his "foreign" wife. Nevertheless, some years into their marriage, Keru and Nate find themselves incorporating their families into two carefully planned vacations. The results are disastrous and revealing. First in a cozy beach house on Cape Cod, and later in a luxury bungalow in the Catskills, the couple is forced to confront the hidden truths at the core of their relationship. Alongside their giant sheepdog Mantou, Keru and Nate navigate visits from in-laws, a sibling, and surprising new friends, all while trying to determine if they have what it takes to make themselves and each other happy. How do you cope when your spouse and your family of origin clash? How many people (and dogs) are needed to make a family? And when the pack starts to disintegrate, what does it take to shepherd everyone back together?"--